Depositional Framework and Stratigraphic Sequence of Early – Middle Miocene succession in Balad and East Baghdad oil fields, Central Iraq - AL- Yassery, Noor Ahmed Noori; Al-Zaidy, Aiad Ali Hussien (Iraqi Journal of Science, 2023)
This study deals with microfacies analysis, diagenetic facies, environmental interpretations related to sequence stratigraphy for Early – Middle Miocene in selected wells within Balad (Ba-X) and East Baghdad (EB-Z) oil fields. Seven major microfacies were recognized in the successions of the study wells, these facies were used to recognize six facies association (depositional environments) within the study oil fields: deep marine, toe of slope, open marine, restricted interior platform, evaporitic interior platform and brackish interior platform. The facies associations interpreted were based on texture and obtainable fauna. The Early - Middle Miocene succession was deposited during two depositional cycles as a third order cycle (C1and C2). These cycles are asymmetrical and started with cycle one (C1) which divided into three sub-cycles in Balad oil field. The first (CS1) deep open marine association facies in lower part of Serikagni Formation represents by relatively thin transgressive system tract (TST). This facies overlying by evaporitic interior platform association facies as highstand system tract (HST) within the upper part of Serikagni Formation and bounded by MFS. The second sub - cycle (CE1) is represented by relatively thin transgressive system tract (TST) reflected by restricted interior platform occupies the lower part of Euphrates formation, while middle and upper part occupies by highstand system tract (HST), which represented by evaporitic interior platform facies. At the lower part of Dhiban Formation sub - cycle (CDh1) is started with transgressive system tract (TST) reflected by Evaporitic interior platform overlying by open marine environment which represent the starting of highstand system trac (HST). Cycle two (C2) is almost symmetrical cycle started with transgressive system tract (TST) reflected by restricted interior platform occupies the lower part of Jeribe Formation, while middle and upper part occupied by highstand system tract (HST), which represented by open marine environment. This succession appeared high cyclicity in East Baghdad oil field during the same two major cycles (C1 and C2) with absence of deep open marine association facies (Serikagni Formation). Where C1 cycle is appeared five sub-cycles of HST overlying the TST within Euphrates and Dhiban succession. The second cycle is characterized by three sub-cycles of HST overlying TST sub-cycle within the Jeribe succession. The above gives accurate evidence that the location of the East Baghdad oil field was the closest to the continental part, while the Balad oil field was towards the deep sea. This clearly affected the number of sedimentation cycles and the shallowness of the deposition environment in the East Baghdad field compared to the Balad oil field.